Political Patronage in Pesantren: Value Transmission and Santri Character Development in Indonesia’s 2024 Presidential Election - Ruzakki, Hasan; Khoiriyah, Siti (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2026)
This study examines the political involvement of pesantren (Islamic boarding schools) during the 2024 Indonesian presidential election and its implications for values education and character development within the pesantren tradition. Employing a qualitative approach and media document analysis, data were collected from online news articles documenting pesantren participation, including support from religious leaders (kiai) and community mobilization. The findings indicate that pesantren play a dual role: as religious institutions providing moral legitimacy and as political actors influencing election outcomes. This duality sparks conflict between the pesantren’s core mission of instilling values, such as moral integrity, independent thinking, and interfaith harmony, and the pragmatic demands of political support. Political involvement can strengthen the pesantren’s social influence and simultaneously risk eroding foundational educational values, creating conflicts of loyalty among students, and weakening the integrity of the character-based learning environment. This study concludes that resolving this tension requires a conscious commitment to separating the institution’s political role from the daily pedagogical processes of value transmission and character development. These findings contribute to the discourse on how religious educational institutions can maintain their character-building mission amid increasing democratic political pressures.